2008
DOI: 10.1016/j.juro.2007.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cystitis is Accompanied by Increased Peripheral Thermal Sensitivity in Mice

Abstract: Purpose-Visceral inflammation and pain associated with chemical cystitis produces increased sensitivity to noxious stimuli within with the sacral dermatomes. This study was performed to determine whether a similar sensitization occurs in response to bacterial cystitis.Materials and Methods-Bacterial cystitis was induced by intravesical instillation of E. coli 1677 in female C57BL/6N (C57) and C3H/OuJ (OuJ) mice. C3H/HeJ (HeJ) mice were used as a control because HeJ mice lack functional toll-like receptor 4 (Tl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Although TLR4 involvement is well documented for bacterial defense it has only recently be implicated in nociception. Similar to the results presented here, one previous study demonstrated enhanced thermal sensitivity in mice infected with bacteria [36]. Furthermore, our study is first, to our knowledge, to demonstrate that LPS is the initiator of UTI-induced pelvic pain.…”
Section: Discussionsupporting
confidence: 91%
“…Although TLR4 involvement is well documented for bacterial defense it has only recently be implicated in nociception. Similar to the results presented here, one previous study demonstrated enhanced thermal sensitivity in mice infected with bacteria [36]. Furthermore, our study is first, to our knowledge, to demonstrate that LPS is the initiator of UTI-induced pelvic pain.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the involvement of TRPV1 afferents in pelvic sensitivity, other receptors and molecules can also contribute to abdominal hyperalgesia depending on the model and nature of chosen inflammatory agents [81]. Thus, increased peripheral sensitivity in mice with bacterial cystitis was related to activation of toll-like receptor 4 [82]. In the acrolein model of bladder inflammation in rats, increased mechanical sensitivity was conveyed, in part, via NGF and trk receptors [83].…”
Section: Discussionmentioning
confidence: 99%
“…to injure the bladder. Evoked pain behaviors, visceromotor response to distension, or secondary hyperalgesia on the abdomen or paw is assessed [19;116;181]. …”
Section: Animal Models Of Diseasementioning
confidence: 99%